2019
DOI: 10.1111/cid.12684
|View full text |Cite
|
Sign up to set email alerts
|

Implant health and factors affecting peri‐implant marginal bone alteration for implants placed in staged maxillary sinus augmentation: A 5‐year prospective study

Abstract: Purpose Evaluating the extent of and the factors affecting marginal bone level (MBL) alterations and consecutively implant success and implant health for implants placed in staged maxillary sinus floor (SF) augmentation. Materials and Methods A 5‐year prospective, cohort study was conducted on 85 patients with 124 maxillary sinus augmentation procedure and 295 implants placed. Peri‐implant MBL alterations (reductions) were evaluated radiographically at the first year, third year, and fifth year postloading fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 37 publications
1
27
3
1
Order By: Relevance
“…The prevalence of patients presenting peri‐implant pathologies was 19.9% (in detail, 10.9% mucositis and 9% peri‐implantitis) with a follow‐up ranging from 1 to 18 years after prosthetic loading (mean follow‐up, 4.6 years). Our findings are slightly higher in comparison with a recent prospective study analyzing implants placed in two‐stage maxillary sinus augmentation, reporting 6.6% patient‐level prevalence of peri‐implantitis 27 . This discrepancy could be likely due to different sample features between the two studies (e.g., 100% two‐stage sinus elevation versus 75% one‐stage).…”
Section: Discussioncontrasting
confidence: 93%
“…The prevalence of patients presenting peri‐implant pathologies was 19.9% (in detail, 10.9% mucositis and 9% peri‐implantitis) with a follow‐up ranging from 1 to 18 years after prosthetic loading (mean follow‐up, 4.6 years). Our findings are slightly higher in comparison with a recent prospective study analyzing implants placed in two‐stage maxillary sinus augmentation, reporting 6.6% patient‐level prevalence of peri‐implantitis 27 . This discrepancy could be likely due to different sample features between the two studies (e.g., 100% two‐stage sinus elevation versus 75% one‐stage).…”
Section: Discussioncontrasting
confidence: 93%
“…Result of linear regression models or simple logistics using generalized estimation equations (GEEs) or chi-square test of independence 16 mm 6 6 (100) 0 (0.0) a total of 7 implants (3.3% of implants) were diagnosed with PI. In a 5-year prospective study, Krennmair and coworkers reported almost the same results, with an implant-level rate of peri-implantitis of 3.3%, and 6.6% at the patient level (Krennmair et al, 2019).…”
Section: F I G U R Ementioning
confidence: 66%
“…In fact, the conclusions on the influence of hyperglycemia on peri-implant inflammation are still heterogeneous. 12 clinical studies (1× cross-sectional study, 5× prospective, 6× retrospective) showed no increased risk of developing peri-implantitis with manifest diabetes mellitus [ 17 , 23 , 24 , 27 , 34 , 38 41 , 44 , 46 , 77 ]. On the other hand, six studies indicated an increased risk of peri-implant inflammation, with the highest determined relative risk being given as 8.65 [ 15 , 28 , 31 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results regarding diabetes and implant survival are heterogeneous. Five studies showed no negative influence [ 10 , 11 , 38 , 42 , 44 ], two showed a non-significant [ 29 , 36 ] and six a significantly negative influence of diabetes on implant survival [ 12 , 16 , 32 , 37 ]. For example, the study of Alberti et al [ 38 ] showed no significant difference of the implant survival after 10 years in patients with diabetes (survival rate of 96.5%) compared to patients without diabetes mellitus (survival rate of 94.8%), whereas the study of French et al [ 37 ] identified diabetes mellitus with a hazard ratio of 2.25 as a risk factor for implant failure in a multivariate analysis, implicating an over two times higher risk for failure of dental implants in patients with diabetes mellitus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation